Effect of external operational damage on the mechanical behavior of GFRP under quasi-static and fatigue loading (Fracture and Structural Integrity, 2026)
An experimental study was conducted to investigate the influence of operational defects, such as surface scratches and dents, on the residual mechanical properties of glass fiber-reinforced plastic (GFRP) during quasi-static tensile and fatigue tests. Based on the results of static tests, the types of simulated defects and loading parameters for cyclic testing were determined. Fatigue tests were performed on groups of samples without defects, with a 10 kN dent, a 15 kN dent, and a scratch. The results of these tests allowed the identification of the most critical type of external damage. The failure of GFRP samples with operational defects was analyzed after both quasi-static tension and fatigue testing. Examination of the fracture surfaces of the fatigue-tested samples revealed that failure occurs primarily at the site of the applied defect due to fiber fracture.
Keywords: Fiberglass; Surface defects; scratch; dent; mechanical behavior; fatigue life